Perceptions of Health Warning Labels on Cigarette Packages: A Study of Bangladesh Smokers - Sultana, Umme Habiba; Yu, Jun; Zhou, Joyce; Sonju, Jafrin Jobayer; Shikha, Sultana Razia (Journal of Applied Business and Economics, 2023)
Health warnings on cigarette packages are among the major sources of information on the negative consequences of smoking. Such labels are especially important for developing countries as there are large populations of smokers in those countries. Effective tobacco warning labels could help reduce tobacco use among smokers and improve their health. The objective of the study is to identify the effects of tobacco warning labels on cigarette packages among adult smokers in Bangladesh, one of the most populous developing countries. Our research indicates that most smokers understand the harmfulness of smoking, more than 90% of them have knowledge about health-related illnesses caused by smoking, and package labels are the second most cited information source after mass media. However, the effectiveness of the warning labels is somewhat lacking. The findings have implications about improving warning labels for the purpose of reducing smoking habits in developing countries.